2020
DOI: 10.1109/jbhi.2019.2950574
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Atrial Fibrillation and Atrial Flutter in Daily Life Using Photoplethysmography Data

Abstract: Objective: Photoplethysmography (PPG) enables unobtrusive heart rate monitoring, which can be used in wrist-worn applications. Its potential for detecting atrial fibrillation (AF) has been recently presented. Besides AF, another cardiac arrhythmia increasing stroke risk and requiring treatment is atrial flutter (AFL). Currently, the knowledge about AFL detection with PPG is limited. The objective of our study was to develop a model that classifies AF, AFL, and sinus rhythm with or without premature beats from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Indeed, we have shown that detecting PAC/PVC can lead to significant false positive reduction during AF detection [ 40 ]. Other recent published reports [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have largely focused on AF without accounting for PAC/PVC and consequently their accuracy of AF detection was suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have shown that detecting PAC/PVC can lead to significant false positive reduction during AF detection [ 40 ]. Other recent published reports [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have largely focused on AF without accounting for PAC/PVC and consequently their accuracy of AF detection was suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the method obtains 95.0% accuracy, 96.2% Sen and 92.8% Spe. Linda et al [14] combined the balance of the PPG characteristics, the interpulse intervals (IPIs) and accelerometer data as input for the RF model. The study categorized AF, AFL and other rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Fallet et al [13] computed the values of multiple parameters, such as the mean, standard deviation, and quartile in PPG, and identified these parameters as inputs to the decision tree model. In the same year, Linda et al [14] combined PPG characteristics, interpulse intervals (IPIs) and accelerometer data in the random forest (RF) model to classify AF, atrial flutter (AFL) and other rhythms. This is a forward-looking study.…”
Section: Introductionmentioning
confidence: 99%
“…As far as AF detection is concerned, two main approaches are used to obtain PPG signals: photodetectors (PD) and cameras [ 37 ]. For PD-based PPG sensors, Bonomi et al and Eerikäinen et al severally used a wrist wearable sensor like a smartwatch with a sampling rate of 128 Hz to collect PPG signals to classify AF and NAF [ 41 , 42 , 43 ]. Barshar et al also used the PD in a smartwatch to collect a PPG signal and detect AF from SR [ 44 ].…”
Section: Instrument/signalmentioning
confidence: 99%